Coffee parchment-derived nanocellulose as reinforcing agent in hydrogel inks for extrusion-based 3D printing of biphasic osteochondral scaffolds - Prakasit Panyamao; Suporn Charumanee; Jetsada Ruangsuriya; Chalermpong Saenjum (Carbohydrate Polymer Technologies and Applications)
Nano-reinforcement plays a crucial role in enhancing the mechanical properties, printability, and structural integrity of hydrogels for scaffold fabrication. This study explores the potential of TEMPO-oxidized nanocellulose (TONCs) derived from coffee parchment as a reinforcing agent in sodium alginate hydrogels for extrusion-based 3D printing of biphasic osteochondral scaffolds. TONCs were synthesized via TEMPO-mediated oxidation using sodium hypochlorite at 5, 10, 15, and 20 mmol/g, yielding cellulose nanofibers (TOCNFs: TONC-5, TONC-10) and cellulose nanocrystals (TOCNCs: TONC-15, TONC-20). Rheological analysis revealed that TONC-10-reinforced hydrogels exhibited the highest yield stress (75.2 Pa), consistency coefficient (323.8 Pa sⁿ), and printability index (0.929), attributed to nanofiber entanglement, ensuring smooth extrusion and filament stability. In contrast, TONC-20-reinforced hydrogels demonstrated greater thixotropic recovery (64.9 %), enabling faster structural reformation due to TOCNCs’ higher carboxylate content and lower aspect ratio, which enhanced electrostatic repulsion, hydration, and ionic crosslinking. Following fabrication, 3D-printed scaffolds reinforced with TONC-20 exhibited superior geometric precision, shape retention, and outstanding performance, including higher water uptake (∼1200 %), diffusion-controlled drug release, improved Young's modulus (227.2 kPa), and excellent biocompatibility, supporting cell proliferation. These findings establish coffee parchment-derived TONCs as sustainable reinforcements for 3D-printed scaffolds, demonstrating that TOCNFs enhance printability and extrusion performance, while TOCNCs improve scaffold stability, mechanical strength, and controlled drug release. This work advances eco-friendly scaffold fabrication for regenerative medicine.